Sunday School success enriching your teaching of the E.T.T.A. course : a guide of practical helps for those teaching the course to teachers and leaders in the church educational program - Bynum, Bill; Evangelical Teacher Training Association (Wheaton, IL Evangelical Teacher Training Association, 1964)
Includes bibliographical references.
Donated by John Dickson, 2002.
Keywords: Sunday school teaching -- techniques